Membangun Super Enkripsi untuk Mengamankan Pesan - Laura Agustina; Imam Sujarwo; Muhammad Khudzaifah (Jurnal Riset Mahasiswa Matematika, 2023)
The issue of message security or an information is very important. A science that studies aboutsecuring the confidentiality of messages using passwords is called cryptography. To enhance security, twoalgorithmsarecombinedtosecuremessages.Superencryptionisaconceptthatusesacombinationoftwoormoresubstitutionandpermutation(transposition)cryptographytechniquestoobtainanalgorithmthatis more difficult to crack. The first thing to do is to encrypt the message using a substitution technique(Cipher Substitution), then re-encrypt it using a permutation technique (Cipher Transposition). In thisstudy, two cryptographic algorithms will be combined to build super encryption using the Vigenere Cipherand Bifid Cipher algorithms to secure messages. The message encryption process is using the VigenereCipher algorithm for the first encryption process, then continued using the Bifid Cipher algorithm for thesecondencryptionprocess.Theencryptionprocessisdonetheotherwayaround,startingfromthebackoftheencryptionprocess.Thecombinationofthesetwoalgorithmsresultsinmoresecuremessagesecurity.